20xcubed-4xsquared-72x=

Simple and best practice solution for 20xcubed-4xsquared-72x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20xcubed-4xsquared-72x= equation:


Simplifying
20xcubed + -4xsquared + -72x = 0

Reorder the terms:
-4adeqrsux + 20bcdeux + -72x = 0

Solving
-4adeqrsux + 20bcdeux + -72x = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-20bcdeux' to each side of the equation.
-4adeqrsux + 20bcdeux + -20bcdeux + -72x = 0 + -20bcdeux

Combine like terms: 20bcdeux + -20bcdeux = 0
-4adeqrsux + 0 + -72x = 0 + -20bcdeux
-4adeqrsux + -72x = 0 + -20bcdeux
Remove the zero:
-4adeqrsux + -72x = -20bcdeux

Add '72x' to each side of the equation.
-4adeqrsux + -72x + 72x = -20bcdeux + 72x

Combine like terms: -72x + 72x = 0
-4adeqrsux + 0 = -20bcdeux + 72x
-4adeqrsux = -20bcdeux + 72x

Divide each side by '-4deqrsux'.
a = 5bcq-1r-1s-1 + -18d-1e-1q-1r-1s-1u-1

Simplifying
a = 5bcq-1r-1s-1 + -18d-1e-1q-1r-1s-1u-1

See similar equations:

| -4(6n-5)+3a= | | -2x+X=20-1 | | 5x-11=17+3x | | -2x-7+6(x+1)=-3x-6 | | X-2+x-3=57 | | 15.2d+7.24=-2.6-2.3d+11.59 | | 5(x-4)+6x=3(1-x) | | -9-3x=-5x+9 | | 1w-4=9-1w | | X+x=22+6 | | 28p=6p^2 | | .65X=9.10 | | 4-10k=34 | | x=4*60-160 | | 5+7(2x+11)+4x= | | 3x-6+8x=2x-3 | | W-4=9-w | | f(x)=-11x+3 | | 7x-7=4(2x-3) | | 12-12y-3(y+2)=4y+6-y | | x^3+40=13 | | 5e^9t=7e^8t | | 9+6=135 | | 2x+(-7+1x)=-1 | | 3x(x+2)=-18 | | -2(y+2)=3y | | 7s-8=64 | | y=17x^3 | | -14-8-6c=12-4c | | x=.25*150+40 | | 15-4(x+3)=19 | | 0.6h=13.032 |

Equations solver categories